2017
DOI: 10.1002/bmb.21051
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate medical academic performance is improved by scientific training

Abstract: The effect of scientific training on course learning in undergraduates is still controversial. In this study, we investigated the academic performance of undergraduate students with and without scientific training. The results show that scientific training improves students' test scores in general medical courses, such as biochemistry and molecular biology, cell biology, physiology, and even English. We classified scientific training into four levels. We found that literature reading could significantly improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Indeed, students’ positive attitudes toward research increased their interest in applying principles they learned to the practice of medicine [17]. Although Chinese medical postgraduates encounter a substantial language obstacle in their academic pursuits [18], our study showed that the English literacy level, which is known as the “College English Teaching (CET)” level in China [19], was note shown to not influence the effectiveness of the course, likely because the college students’ English literacy level has significantly improved in China in recent years [20].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, students’ positive attitudes toward research increased their interest in applying principles they learned to the practice of medicine [17]. Although Chinese medical postgraduates encounter a substantial language obstacle in their academic pursuits [18], our study showed that the English literacy level, which is known as the “College English Teaching (CET)” level in China [19], was note shown to not influence the effectiveness of the course, likely because the college students’ English literacy level has significantly improved in China in recent years [20].…”
Section: Discussionmentioning
confidence: 98%
“…Since student research training program was initiated at Tsinghua University in 1996, SRT program became a principal approach for college students to improve their skills and ability to innovate. As a result, both academic and nonacademic performance of medical undergraduates were signi cantly improved by planned SRT program [10,13]. Thus, early SRT program played an important role in promoting scienti c performance and innovation ability of undergraduates.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to scientific training improved academic performance; enhanced students' motivation; and improved students' confidence in their learning. 92 A study of the use of software to build representations of molecular structures found this activity to be more beneficial than just manipulating images they were given, but did not have any effect on students' motivation. 93…”
Section: Students' Attitudes/motivation and Self-confidence In Bioche...mentioning
confidence: 99%
“…The students also expressed interest in using blended learning as a tool for communication with fellow students in the biochemistry class . A study of Chinese undergraduate medical students looked at the effect of different approaches to “scientific training.” Exposure to scientific training improved academic performance; enhanced students’ motivation; and improved students’ confidence in their learning …”
Section: Student Understanding and Other Characteristicsmentioning
confidence: 99%